Carbon Monoxide Activation by a Molecular Aluminium Imide: C−O Bond Cleavage and C−C Bond Formation. (18th February 2020) - Heilmann, Andreas; Hicks, Jamie; Vasko, Petra; Goicoechea, Jose M.; Aldridge, Simon
Abstract: Anionic molecular imide complexes of aluminium are accessible via a rational synthetic approach involving the reactions of organo azides with a potassium aluminyl reagent. In the case of K2 [(NON )Al(NDipp)]2 (NON =4, 5‐bis(2, 6‐di iso propylanilido)‐2, 7‐di‐tert‐butyl‐9, 9‐dimethyl‐xanthene; Dipp=2, 6‐di iso propylphenyl) structural characterization by X‐ray crystallography reveals a short Al−N distance, which is thought primarily to be due to the low coordinate nature of the nitrogen centre. The Al−N unit is highly polar, and capable of the activation of relatively inert chemical bonds, such as those found in dihydrogen and carbon monoxide. In the case of CO, uptake of two molecules of the substrate leads to C−C coupling and C≡O bond cleavage. Thermodynamically, this is driven, at least in part, by Al−O bond formation. Mechanistically, a combination of quantum chemical and experimental observations suggests that the reaction proceeds via exchange of the NR and O substituents through intermediates featuring an aluminium‐bound isocyanate fragment. Abstract : C‐C‐Kupplung : Es wurde festgestellt, dass ein isolierbares molekulares Aluminiumimid mit einer hochpolarisierten Al‐N‐Bindung über C≡O‐Bindungsspaltung und C‐C‐Kupplung mit CO reagiert. Die wichtigsten vorgeschlagenen Zwischenprodukte bei dieser Umwandlung weisen ein aluminiumgebundenes Isocyanatfragment auf